Study on γδT-Cell Degranulation at Maternal–Fetal Interface via iKIR–HLA-C Axis - Diana Manchorova; Marina Alexandrova; Antonia Terzieva; Ivaylo Vangelov; Ljubomir Djerov; Iana Hristova; Gil Mor; Tanya Dimova (Cells)
Maternal–fetal tolerance mechanisms are crucial during human pregnancy to prevent the immune rejection of the embryo. A well-known mechanism blocking NK-cell cytotoxicity is the interaction of their inhibitory killer-cell immunoglobulin-like receptors (iKIR) with HLA-C molecules on the target cells. In this study, we aimed to investigate the expression of iKIRs (KIR2DL1 and KIR2DL2/3) on the matched decidual and peripheral γδT cells and the localization of HLA-C ligands throughout human pregnancy. The degranulation of γδT cells of pregnant and non-pregnant women in the presence of trophoblast cells was evaluated as well. Our results showed a higher proportion of iKIR-positive γδT cells at the maternal–fetal interface early in human pregnancy compared to the paired blood of pregnant women and full-term pregnancy decidua. In accordance, HLA-C was intensively expressed by the intermediate cytotrophoblasts and decidua-invading extravillous trophoblasts (EVTs) in early but not late pregnancy. Decidual γδT cells during early pregnancy showed higher spontaneous degranulation compared to their blood pairs, but neither decidual nor peripheral γδ T cells increased their degranulation in the presence of Sw71 EVT-like cells. The latter were unable to suppress the higher cytotoxicity of γδT cells, suggesting a complex regulatory landscape beyond NK-like activity inhibition.